Chip Product Development Based on Business Management and Creativity Training in Magelang District - Hassani , Rofi Abul; Tidar , Zidan Zakaria; Alfiyanto, Dwi Janu; Marella , Mita; Saputri , Cindy Febrina Eka; Septiana , Syahadenita Eka (Universitas Muhammadiyah Surakarta, 2023)
This activity aims to overcome the problems faced by partners where these problems make it difficult for partners to develop. The culinary chip industry is one of the businesses owned by the residents of Wonogiri Lor Hamlet, Kapuhan Village, Sawangan District, the majority of the population of Wonogiri Lor Village are farmers. As for the business partner sector itself, it is a culinary industry in the form of various chips which usually consist of mushroom, intestine, bitter melon, spinach, melinjo chips, and so on. Based on information extracted from business owners, there are at least four problems faced by partners, namely: lack of knowledge about management, especially marketing management, product packaging that usually only uses ordinary plastic, no business licensing, and efforts to increase revenue. The aspect of capital which has been an important problem for a business entity, in this case partners, is also constrained regarding capital because the capital used by partners is their own capital so they have not received capital support from the village or from the district government. In overcoming these problems, we try to provide solutions by targeting the Human Resources (HR) aspect. HR is one of the important aspects in an organization because it is HR that runs other aspects of an organization. We are trying to strengthen the human resources of partner organizations by providing several programs such as providing business management training, marketing training for chips culinary business partners to strengthen human resources and marketing chips for Mrs. Ana's industrial business.